First, let's simplify the left side of the equation using the Distributive Property:
2(x-5) = 2 * x - 2 * 5 = 2x - 10.
Now let's simplify the right side of the equation by combining like terms:
9 - 3x + 6 + 8 + 3x + 7 = (9 + 6 + 8 + 7) - 3x + 3x = 30.
So the simplified equation is 2x - 10 = 30.
For the equation 2(x−5)=9−3x+6+8+3x+7
, the left side of the equation can be simplified using the Distributive Property, and the right side of the equation can be simplified by combining like terms. (2 points)
1 answer